The Influence of Big Book Activity-Based Role-Playing on the Social Skills Of Children Aged 5-6 Years in Tutor Time Intercon Kindergarten - Yuanita, Satia Imelda; Puridawaty, Brigita (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to determine the extent of the effect of Big Book Activity-based role-playing on the social skills of children aged 5-6 years in Time Intercon Kindergarten Tutors. This study is quantitative research by paying attention to and revealing the extent of the influence of Big Book Activities-based role-playing on the social skills of children aged 5-6 years in Time Intercon Tutor Kindergarten by comparing the learning outcomes of experimental classes with control classes. The experimental class was given action (X) while the control class was given action (Y) Students involved in this study were Group B Class B1 and B2, with a total of 30 students. Class B1 is an experimental class using the learning process by role-playing using Big Book Activities, while class B2 uses conventional learning. Techniques in collecting data using research instruments in the form of indicators that will be achieved as many as 15 items, which are carried out through action tests. The statistical program used for all statistical analysis in analyzing the data obtained during the study used SPSS 20.0, using normality, homogeneity, and hypothesis tests. Based on data analysis, the post-test results of the experimental class were greater than the control class, namely 75.55 for the experimental class and 50.22 for the control class. The resulting data is normally distributed and homogeneous. The Independent Sample T Test (mean) in the experimental class was 75.55 greater than the mean in the control class of 50.22. So it can be concluded that there is a significant influence of big book activity-based role-playing on the social skills of children aged 5-6 years in Tk Tutor Time Intercon.